2019
DOI: 10.1002/maco.201910777
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution corrosion of 4H‐SiC in lead‐bismuth eutectic at 550°C

Abstract: The corrosion behavior of 4H-SiC in lead-bismuth (Pb-Bi) eutectic (LBE) at 550°C is investigated. To clarify the effect of irradiation damage on corrosion, samples with and without Si 5+ ion irradiation are contrastively evaluated. The main results show that dissolution corrosion occurs in both unirradiated and irradiated samples, while the irradiation damage can accelerate the corrosion rate. The corroded surface is characterized by the loss of C element and the formation of amorphous layers with a slight enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Similar results were also reported by Lillard et al [270] and Yao et al [271]. In addition to enhanced oxidation, Li et al [272] reported that 4H-SiC was subjected to enhanced dissolution corrosion in oxygen-saturated LBE at 550 • C for 167 h of exposure, after irradiation up to 1.6 dpa at RT with 880 keV Si 5+ ions.…”
Section: The Role Of Irradiationsupporting
confidence: 84%
“…Similar results were also reported by Lillard et al [270] and Yao et al [271]. In addition to enhanced oxidation, Li et al [272] reported that 4H-SiC was subjected to enhanced dissolution corrosion in oxygen-saturated LBE at 550 • C for 167 h of exposure, after irradiation up to 1.6 dpa at RT with 880 keV Si 5+ ions.…”
Section: The Role Of Irradiationsupporting
confidence: 84%
“…Takahashi 13 F I G U R E 1 4 Results of the SEM-energy dispersive spectrometer (EDS) line scan of cross-section of the SiC impeller after corrosion reported that the weight loss of the SiC specimen was 13.2 g/m 2 during his corrosion test, and the corrosion mechanism could be described by the following reaction equation, SiC + 2PbO → SiO 2 + 2Pb + C. Moreover, a cracked layer appeared on the SiC specimen, which was due to the shear and normal stress of the fast-flowing LBE. 25 Besides, Li 14 pointed out that the LBE corrosion of SiC was characterized by the formation of an amorphous layer on the corroded surface, which was caused by the loss of C element and the enrichment of Si element. Lei 15 confirmed that element C wa dissolved more easily than element Si on SiC surface in LBE, and the depletion of C might lead to the formation of a layer of amorphous Si.…”
Section: Dynamic Lbe Corrosionmentioning
confidence: 99%
“…SiC ceramic was regarded as a candidate of the cooling pump impellers of accelerator-driven systems and Gen-IV lead-cooled fast reactors [1][2][3] due to its many excellent properties such as irradiation resistance, corrosion resistance, high-temperature strength, high-temperature creep resistance, oxidation resistance, and neutron transparency. [4][5][6][7][8][9] Although some scholars studied the compatibility of SiC bulk ceramics with LBE, 1,[10][11][12][13][14][15] there were no reports on the dynamic corrosion behavior of SiC impellers in the liquid lead-bismuth eutectic (LBE) alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation